Understanding Farmers’ Information Needs on Crop-Tree Intercropping: An Analysis of Poplar Tree-Related Helpline Calls in India - Godara, Shruti; Yadav, Shambhavi; Bana, Ram Swaroop; Kantwa, SR; Godara, Samarth (Indian Journal of Agroforestry, 2025)
To tackle the challenges in enhancing livelihoods of tree growers, it is obligatory to integrate cutting-edge methodologies such as Big Data analysis and Artificial Intelligence into the domain of Agroforestry. In this direction, this research paper presents an in-depth analysis of the helpline data/call logs collected from Indian farmers from 2006 to 2023, focusing on their inquiries about poplar tree farming as tree + crop intercropping. The study aims to provide valuable insights into the patterns and trends of farmers’ interactions with the helpline service over the past 17 years. The research methodology involved a descriptive analysis of the dataset, including state-wise categorisation of calls, identification of frequently discussed topics, examination of years of call log patterns and analysis of the monthly distribution of queries. The findings of this study reveal that farmers from Uttar Pradesh, Haryana, and Uttarakhand demonstrate the highest level of engagement, in seeking information and assistance pertaining to poplar trees. Notably, topics related to plant protection and cultural practices garner the greatest interest among farmers. Furthermore, a significant influx of inquiries occurs during the months of January and May. The findings from this study contribute to a better understanding of the issues faced by Indian farmers concerning poplar trees and provide valuable insights for policymakers, agricultural experts, and helpline service providers. By uncovering the prevalent concerns and temporal patterns, appropriate measures and resources can be allocated to address the specific needs of farmers effectively. Overall, this research contributes to the body of knowledge surrounding farmer helpline services and serves as a foundation for further research and targeted interventions to enhance agricultural support systems.